A novel thiophene‐3‐carboxamide analog of annonaceous acetogenin exhibits antitumor activity via inhibition of mitochondrial complex I. Issue 4 (12th July 2016) - Akatsuka, Akinobu; Kojima, Naoto; Okamura, Mutsumi; Dan, Shingo; Yamori, Takao
Abstract: Previously we synthesized JCI‐20679, a novel thiophene‐3‐carboxamide analog of annonaceous acetogenins which have shown potent antitumor activity, with no serious side effects, in mouse xenograft models. In this study, we investigated the antitumor mechanism of JCI‐20679. The growth inhibition profile (termed "fingerprint") of this agent across a panel of 39 human cancer cell lines (termed "JFCR39") was measured; this fingerprint was analyzed by the COMPARE algorithm utilizing the entire drug sensitivity database for the JFCR39 panel. The JCI‐20679‐specific fingerprint exhibited a high similarity to those of two antidiabetic biguanides and a natural rotenoid deguelin which were already known to be mitochondrial complex I inhibitors. In addition, the fingerprint exhibited by JCI‐20679 was not similar to that displayed by any typical anticancer drugs within the database, suggesting that it has a unique mode of action. In vitro experiments using bovine heart‐derived mitochondria showed direct inhibition of mitochondrial complex I by JCI‐20679 and associated derivatives. This inhibition of enzymatic activity positively correlated with tumor cell growth inhibition. Furthermore, a fluorescently labeled derivative of JCI‐20679 localized to the mitochondria of live cancer cells in vitro. These results suggest that JCI‐20679 can inhibit cancer cell growth by inhibiting mitochondrial complex I. Our results show that JCI‐20679 is a novel anticancer drug lead with a unique mode of action.